Our world by the numbers - Jenkins, Steve, 1952-2021 (Jenkins, Steve, 1952-2021. By the numbers., 2024)
"With his signature style, Steve Jenkins uses engaging graphics and visual literacy to convey scientific facts and concepts, making them accessible for all kinds of readers. In Our World: By the Numbers readers will learn about the complex and wonderful place we call home. This book opens wide on the solar system and then zooms in on planet Earth--its history, its creatures, its climate, and its future. Discover some of the most fascinating aspects of our world through astonishing numbers: the stretch of time from Earth's formation to the present, how often lightning strikes in one day, the temperature at the center of the sun, what percentage of Earth's land is covered in deserts or forests or cities, and so much more. This compendium is ideal for curious young readers, with fact-packed and image-driven pages detailing the astonishing phenomena that make our universe such an incredible place to live."--Provided by publisher.